Impact of adenotonsillectomy in pediatric patients with obstructive sleep apnea - Linhares de Castro, Ana Caroline; Damasceno Inácio , Natania Tuanny; do Nascimento Andrade Feitosa, Ankilma; de Andrade Isidorio, Ubiraídys (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Introduction: Obstructive Sleep Apnea (OSA) is a common respiratory disorder in childhood, characterized by recurrent upper airway obstructions during sleep. The main symptoms include snoring, breathing pauses, and daytime sleepiness, which can negatively impact neurocognitive development and behavior. Adenotonsillar hypertrophy is the primary cause of OSA in children. Objective: To analyze, through an integrative literature review, the effects of adenotonsillectomy (AT) on reducing the symptoms of Obstructive Sleep Apnea in pediatric patients. Methods: An integrative literature review was conducted using the PubMed, LILACS, SciELO, BVS, and Google Scholar databases. The search employed the descriptors “Obstructive Sleep Apnea,” “Children,” and “Adenotonsillectomy,” covering the period from 2019 to 2024, and used the Boolean operator “AND.” After applying inclusion and exclusion criteria, 9 relevant articles were selected. Results and Discussion: The reviewed studies indicate that AT is effective in reducing the apnea-hypopnea index (AHI) and improving the quality of life in children with OSA. However, residual symptoms were observed in some cases, particularly among patients with comorbidities such as obesity, genetic syndromes, or craniofacial anomalies. In these situations, additional strategies—such as CPAP therapy, orthodontic treatment, and lifestyle modifications—are recommended. Emerging technologies, including artificial intelligence, also show potential in enhancing early diagnosis and personalized treatment. Conclusion: Adenotonsillectomy is generally effective in treating pediatric OSA, resulting in both clinical and functional improvements. Nevertheless, a personalized and multidisciplinary approach is essential, especially in complex cases, to ensure comprehensive management of pediatric OSA.